Induced mutagenic effectiveness and efficiency studies on Pigeon pea (Cajanus cajan (L.) Millsp). - Ariraman, M.; Bharathi, T.; Dhanavel, D. (Food Biology, 2016)
The present investigation was carried out to study mutagenic effectiveness and efficiency of gamma rays and EMS treatments in Pigeon pea (CajanusÂ cajan (L.) Millsp) Var CO-7. The relative effectiveness and efficiency of the both mutagen used was assessed from the data on biological damage in M1 generation and frequency of chlorophyll and viable mutants in M2 generation. The spectrum of chlorophyll mutants such as xantha, albino, chlorina and viridis, viable mutants like tall, dwarf, early flower, early maturity, late maturity, bushy, high yield and seed mutants were observed in both the mutagenic treatments.Â Among the chlorophyll mutants xantha was found more in number. The mutagenic effectiveness and efficiency were found to be higher at 20KR of gamma irradiation and 25mM of EMS. The mutation rate of gamma rays was higher in terms of effectiveness than that of EMS. More number of chlorophyll and viable mutants was induced in gamma rays treatment when compared EMS treatment.